2001
DOI: 10.1159/000050937
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Gleason Scores from Sextant Prostate Biopsies and Radical Prostatectomy Specimens

Abstract: Objectives: We compared the Gleason scores obtained from sextant prostate biopsy and radical prostatectomy (RP) specimens in patients with localized prostate cancer. Patients and Methods: Sixty-one patients having a clinical diagnosis of localized prostate cancer underwent needle biopsy under transrectal ultrasonography (TRUS) and RP. Grading and staging were assigned based on Gleason scores and the TNM system, respectively. Results: Mean patient age was 65.5 ± 13.43 years and mean PSA level was 14.69 ± 3.95. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
(16 reference statements)
1
8
1
Order By: Relevance
“…Smaller lesions are less likely to be detected and would also have lower likelihood of clinical signifi cance [ 22 -24 ] . This has been reported previously, though it was noted to be dependent on the biopsy scheme [ 15,16,25,26 ] . While it is conceivable that treating the DV only by focal therapy is suffi cient for good outcomes, it is equally likely the small DG lesions, which are more frequently missed, are inevitably responsible for prostate cancer morbidity and mortality.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Smaller lesions are less likely to be detected and would also have lower likelihood of clinical signifi cance [ 22 -24 ] . This has been reported previously, though it was noted to be dependent on the biopsy scheme [ 15,16,25,26 ] . While it is conceivable that treating the DV only by focal therapy is suffi cient for good outcomes, it is equally likely the small DG lesions, which are more frequently missed, are inevitably responsible for prostate cancer morbidity and mortality.…”
Section: Discussionsupporting
confidence: 72%
“…consistently low levels of accuracy that did not exceed those found in our study [ 3,8,11,12,20,21,25,26 ] . A previous study reported that increasing the number of cores taken per biopsy increases the detection rate of prostate cancer [ 25 ] .…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…In fact, various studies have recently reported that the Gleason score of biopsy specimens was identical to the score of prostatectomy specimens in less than 50% of cases examined [14,15]. This discordance may possibly explained by several factors, such as pathological interpretation bias and different procedure of systematic biopsy.…”
Section: Discussionmentioning
confidence: 98%
“…The Gleason score combined with the determination of serum PSA and the findings of the standard digital prostate exam can predict the tumor stage and the occurrence of lymph node metastasis (Landis,1977). However, studies have shown discrepancies between biopsy score and score of tissue specimens submitted to anatomopathological analysis following radical prostatectomy (Altay, 2001;Gregori, 2001;Prost,2001). The under-estimation of the Gleason score after a biopsy is a common occurrence in patients with prostate adenocarcinoma, with rates reported in the literature ranging from 32.4 to 46.6% (Tavangar, 2004;Montesino,2004).…”
Section: Discussionmentioning
confidence: 99%